Prevalence of needle stick injuries and compliance to infection control guidelines among health care workers in a teaching hospital, Malaysia - Abd. Hamid, Mohd. Zaini; Aziz, Noor Azah; Lim, W. B.; Salleh, S. L. M.; Rahman, S. N. S.; Abdul Rahman, Anita; Othman, Norlijah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2011)
Introduction: Health care workers (HCW) are constantly exposed to blood-borne illnesses through needle stick injuries (NSI). Despite the increasing trend of NSI, evidence regarding the actual practice of universal precautions among these HCWs is lacking. This study assessed the practice of universal precautions towards prevention of NSI among HCWs in a teaching hospital setting. Methods: This cross-sectional survey involved a newly-designed self-completed questionnaire assessing demographic data, exposure to NSI and practice of universal precautions. Questionnaires were distributed to every ward and completed questionnaires were collected after a period of 7 days. Results: A total of 215 HCWs responded to the survey. 35.8% were exposed to bodily fluid, with 22.3% had NSI in the last 12 months. Blood taking was the commonest procedure associated with NSI. Of practices of universal precautions, recapping needle and removing needle from syringe were still wrongly practiced by the HCWs assessed. Conclusion: NSI among HCW are still common despite the introduction of universal precautions in our hospital. Incorrect practices in handling sharps should be looked into in order to reduce the incidence of blood-borne illnesses through NSI in the hospital.